PENINGKATAN DAYA SAING UKM FURNITURE SUMATERA BARAT MELALUI PERANCANGAN APLIKASI BERBANTUAN KOMPUTER - Lusi Susanti; Prima Fithri; Difana Meilani; Hilma Raimona Zadry; Dina Rahmayanti; Reinny Patrisina (Jurnal Hilirisasi IPTEKS, 2020)
Most of the furniture industries / SMEs in West Sumatra still use the traditional cost system in calculating the cost of goods manufactured. In addition, furniture SMEs in West Sumatra still use technology to make it easier to process data. In addition, in other studies it was found that in Indonesia the use of information technology by SMEs is still low compared to large companies. Even though the use of information technology can increase the competitiveness of SMEs. Many things have caused the low use of information technology by SMEs. One of them is the lack of knowledge of the potential of information technology to advance business. Therefore, the importance of using information technology to increase the competitiveness of SMEs, and the need to use the ABC method in calculating the cost of production, the Department of Industrial Engineering, Andalas University provides assistance, training, and coaching to furniture SMEs in West Sumatra. With this activity it will make it easier for SMEs to manage direct raw material costs, direct labor costs, overhead costs and calculate activity-based cost of production as well as make it easier for SMEs to produce activity-based cost of production reports using computer-assisted software, so that SME furniture competitiveness is created. higher level to be able to win the competition and create a better pattern of university partnerships.